INVESTIGATING THE IMPORTANCE OF YOUTH CULTURE IN SUCCESSFUL YOUTH EVENTS - Miffling, Kirsten; Taylor, Ruth (The journal of contemporary issues in business and government, 2007)
Youth are an easily identifiable market, relatively homogenous, highly aural and visual, globally connected and increasingly technologically dependent, seeking to display image and belonging. This paper presents the findings of an empirical study investigating youth events using stakeholder theory, in particular the distinctive elements of youth culture that contribute to the staging of a successful youth event. A case approach was adopted for this study at an extreme/action sports festival staged in Western Australia. The methodology incorporated qualitative pre-event focus groups and in-depth interviews followed by a quantitative questionnaire survey administered using a random intercept method (N=182). The results highlight the importance of youth subculture in the staging of successful youth events. This includes the incorporation of a combination of sport, music/bands, interactivity and atmosphere. The results of the findings have implications for public and private event providers, event planners and policy makers who actively support and assist in the funding of youth events.